2011
DOI: 10.1111/j.1439-0426.2011.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on ultrastructure and motility parameters of spermatozoa of tetraploid and hexaploid Siberian sturgeon Acipenser baerii

Abstract: Siberian sturgeon Acipenser baerii is supposed to by species of functionally tetraploidy (4n). Large-scale screening of ploidy levels of various sturgeon stocks revealed one hexaploid (6n) male specimen producing triploid spermatozoa. Spermatozoa of three tetraploid individuals were compared with those of the hexaploid specimen in terms of ultrastructure and motility features. All evaluated morphometrical characteristics of the acrosome, the head, the midpiece and the flagellum showed significantly higher valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…High rates of spermatozoa motility indicated high quality of sperm and corresponded with high viability. The initiation of spermatozoa velocity (in 15 sec) of the hexaploid A. baerii was lower than reported for males of normal ploidy level, as also observed by Pšenička et al [42]. The authors considered the higher relative DNA content and larger size of heads of the hexaploid A. baerii spermatozoa to be the cause of the difference.…”
Section: Resultsmentioning
confidence: 47%
“…High rates of spermatozoa motility indicated high quality of sperm and corresponded with high viability. The initiation of spermatozoa velocity (in 15 sec) of the hexaploid A. baerii was lower than reported for males of normal ploidy level, as also observed by Pšenička et al [42]. The authors considered the higher relative DNA content and larger size of heads of the hexaploid A. baerii spermatozoa to be the cause of the difference.…”
Section: Resultsmentioning
confidence: 47%
“…Spermatozoa produced by tetraploid male oysters (Dong et al, ) and mussels (Komaru et al, ) have been shown to possess more mitochondria than those produced by diploid males. Presence of higher numbers of mitochondria was reported in spermatozoa of hexaploid male Siberian sturgeon Acipenser baeri compared with tetraploid males (Pšenička et al, ). Our previous work also reported a significantly higher mitochondrial mass per cell and ATP content in diploid sperms of neo‐tetraploid male loaches (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…Pooled‐sperm samples ( n = 20 sperm cells) were used for the study of the morphology of spermatozoa from B. sharpeyi . Semen samples were fixed in a combination (1:1) of 2.5% glutaraldehyde and 0.2 N cacodylate buffer at pH 7.4 (Psenicka, Kaspar, Rodina, Gela, Hulak & Flajshans ). After 2 h of fixation, samples were washed three times for 1 h in fresh 0.2 N cacodylate buffer, then washed repeatedly for 1 h at 4°C in a 1:1 mixture of 1% osmium tetroxide (Gopalakrishnan, Ponniah & Lal ; Alavi et al .…”
Section: Methodsmentioning
confidence: 99%